2007
DOI: 10.1529/biophysj.106.098673
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Detection of Thermogenesis in a Single HeLa Cell

Abstract: We report here the technique for detection and measurement of the temperature changes in single cells using a recently devised microthermometer (a glass micropipette filled with the thermosensitive fluorescent dye Europium (III) thenoyltrifluoroacetonate trihydrate). We found that the heat production in a single HeLa cell occurred with some time delay after the ionomycin-induced Ca(2+) influx from the extracellular space. The time delay inversely depended on extracellular [Ca(2+)], and the increase in temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
151
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(159 citation statements)
references
References 16 publications
8
151
0
Order By: Relevance
“…1SU4 is a conformation where Ca 2+ is present (E1 state), whereas 1KJU is a conformation corresponding to the Ca 2+ -free (E2) state. It has been recently found that ATPases release heat when they are transporting Ca 2+ , 8 hence knowledge of the thermal transport properties is needed to characterize the heat transfer in these enzymes. The protein interactions were modeled using the GROMOS96 43a2 force field.…”
Section: Computer Simulations Of the Proteinsmentioning
confidence: 99%
“…1SU4 is a conformation where Ca 2+ is present (E1 state), whereas 1KJU is a conformation corresponding to the Ca 2+ -free (E2) state. It has been recently found that ATPases release heat when they are transporting Ca 2+ , 8 hence knowledge of the thermal transport properties is needed to characterize the heat transfer in these enzymes. The protein interactions were modeled using the GROMOS96 43a2 force field.…”
Section: Computer Simulations Of the Proteinsmentioning
confidence: 99%
“…[1][2][3][4] Accurately measuring intracellular temperature may provide new insights into cellular signaling and metabolism. However, sensing intracellular temperature is not a trivial task, especially at the single-cell level.…”
Section: Introductionmentioning
confidence: 99%
“…However, sensing intracellular temperature is not a trivial task, especially at the single-cell level. 3 Currently, there are two major approaches to intracellular temperature sensing: one uses micro-or nano-scale thermocouples 1,5 ; the other employs temperature-sensitive fluorescent dyes, 6,7 proteins, 8 or nanoparticles. 9,10 Although the thermocouple-based approach features high-temperature resolution (∼0.1°C), 5 to detect intracellular temperature changes, the tip of the thermocouple has to be inserted into cells via a micromanipulation system.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several approaches have been proposed to detect cellular temperature response using the emission intensity or lifetime of organic dyes (Chapman et al, 1995;Gota et al, 2009) and transition metal ions (Zohar et al, 1998;Suzuki et al, 2007). These pioneering works were able to provide the average temperature for individual cells.…”
Section: Approaches To Monitoring Of Intracellular Temperaturementioning
confidence: 99%